2017
DOI: 10.4103/2230-8229.197180
|View full text |Cite
|
Sign up to set email alerts
|

Acne vulgaris: Perceptions and beliefs of Saudi adolescent males

Abstract: INTRODUCTION:Although acne vulgaris is common in adolescents, information on their understanding of acne is minimal.OBJECTIVES:To evaluate the perceptions and beliefs of Saudi youth on acne.MATERIALS AND METHODS:Three hundred twenty-nine male students (aged 13–22 years) from 6 secondary schools in the Eastern Saudi Arabia completed a self-reported questionnaire on knowledge, causation, exacerbating and relieving factors of acne. Data were analyzed by SPSS version 15.0. Results of subjects with acne, a family h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
(81 reference statements)
0
18
0
Order By: Relevance
“…In this study, information on OIT among patients was obtained most frequently from friends, followed by family, internet, and physicians. Other recent studies have also found that family and friends are often consulted about acne (Al-Natour, 2017;Karciauskiene et al, 2015;Nguyen et al, 2016;Rigopoulos et al, 2007;Szepietowski et al, 2018). Saudi adolescent males and patients from United States reported the sources of information on acne, mostly mass media and internet in a different two studies (Al-Natour, 2017;Nguyen et al, 2016).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In this study, information on OIT among patients was obtained most frequently from friends, followed by family, internet, and physicians. Other recent studies have also found that family and friends are often consulted about acne (Al-Natour, 2017;Karciauskiene et al, 2015;Nguyen et al, 2016;Rigopoulos et al, 2007;Szepietowski et al, 2018). Saudi adolescent males and patients from United States reported the sources of information on acne, mostly mass media and internet in a different two studies (Al-Natour, 2017;Nguyen et al, 2016).…”
Section: Resultsmentioning
confidence: 98%
“…Other recent studies have also found that family and friends are often consulted about acne (Al-Natour, 2017;Karciauskiene et al, 2015;Nguyen et al, 2016;Rigopoulos et al, 2007;Szepietowski et al, 2018). Saudi adolescent males and patients from United States reported the sources of information on acne, mostly mass media and internet in a different two studies (Al-Natour, 2017;Nguyen et al, 2016). There are several reports which indicated the mass media especially internet as a popular source of information for patients (Brajac et al, 2004;Gokdemir, Fisek, Köslü, & Kutlubay, 2011;Szepietowski et al, 2018).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It has a direct impact on our self-esteem and ability to function with confidence. One of the most intriguing facts of physical appearance is acne and it is a phenomenon which has affected all of us at some point in our lives (7)(8)(9)(10)(11)(12). This aspect is of particular importance to teenagers and young adults who are constantly influenced by media to have a certain physical appearance in order to be accepted by their peers and society.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…This aspect is of particular importance to teenagers and young adults who are constantly influenced by media to have a certain physical appearance in order to be accepted by their peers and society. (7)(8)(9)(10)(11)(12) Despite having such a pervasive impact, there are certain areas of this topic that are not given the attention they rightfully deserve. There have been extensive amount of research done on medication and other remedial actions to cure acne.…”
Section: Issn: 2320-5407mentioning
confidence: 99%